DEVELOPMENT OF QUALITY INDEX METHOD TO ASSESS FRESHNESS AND SHELF LIFE OF BLACK TIGER SHRIMP (PENAEUS MONODON) STORED AT 0 °C - Tam, Le Nhat; Giao, Nguyen Nam; Nhung, Tran Thi Ngoc; Duyen, Dao Bich; Nhung, Le Thi Hong; Thanh, Nguyen Ba; Thi, Tran Thi Van (Hue University Journal of Science: Natural Science, 2017)
Black tiger shrimp (Penaeus monodon) was harvested and stored at 0 °C for study. A quality index method (QIM) developed to evaluate the freshness of black tiger shrimp is presented in this study. The terms used to describe all the changes related to the texture, colour, and odour are carefully chosen. The development of the QIM scheme includes three main steps: a preliminary scheme to evaluate all the changes of attributes related to quality; a final QIM scheme and training; and a validation of the QIM scheme and an estimation comparing the remaining shelf life and the actual shelf life. The results show that the shelf life of the black tiger shrimp in the ice storage is 8 days. The quality score involving attributes decreases with the storage time and has a correlation close to the linear regression equation. The scheme of the validation quality of the black tiger shrimp using the QIM method allows the estimation of the remaining shelf life.